Ozone therapy effect in medication-related osteonecrosis of the jaw as prevention or treatment: microtomographic, confocal laser microscopy and histomorphometric analysis - Pereira-Silva, Maísa [UNESP]; Hadad, Henrique [UNESP]; de Jesus, Laís Kawamata [UNESP]; de Freitas Santana Oliveira, Maria Eduarda [UNESP]; de Almeida, Juliano Milanezi [UNESP]; Nímia, Heloisa Helena [UNESP]; Magro Filho, Osvaldo [UNESP]; Okamoto, Roberta [UNESP]; Macedo, Sérgio Bruzadelli; Palmieri Junior, Celso Fernando; Souza, Francisley Ávila [UNESP] (Springer Nature, 2024)
Objective: This study aimed to evaluate the efficacy of ozone therapy in the preoperative (prevention) and/or postoperative (treatment) of MRONJ. Material and methods: Forty male Wistar rats were caudally treated with zoledronic acid (ZOL) and to ozone therapy before extraction (prevention, POG), after extraction (treatment, TOG), or both (prevention and treatment, TPOG), and treated with saline (SAL). The animals received intramuscular fluorochrome (calcein and alizarin), and 28 days postoperatively, they were euthanized, and the tissues were subjected to microtomographic computed tomography (microCT), LASER confocal, and histomorphometric analyses. Results: Micro-CT showed a higher bone volume fraction average in all groups than that in the ZOL group (P < 0.001), the ZOL group showed high porosity (P = 0.03), and trabecular separation was greater in the TOG group than in the POG group (P < 0.05). The mineral apposition rate of the POG group was high (20.46 ± 6.31) (P < 0.001), followed by the TOG group (20.32 ± 7.4). The TOG group presented the highest mean newly formed bone area (68.322 ± 25.296) compared with the ZOL group (P < 0.05), followed by the SAL group (66.039 ± 28.379) and ZOL groups (60.856 ± 28.425). Conclusions: Ozone therapy modulated alveolar bone repair in animals treated with ZOL, mainly after surgery trauma, leading to bone formation as healing tissue. Clinical relevance: Osteonecrosis has been a challenge in dentistry, and owing to the lack of a consensus regarding therapy, studies presenting new therapies are important, and ozone has been one of the therapies explored empirically.
Keywords: Bisphosphonates; Dental alveolus; Osteonecrosis; Ozone